Impact of aeration on plant growth-promoting rhizobacteria assisted phytoremediation capability of arsenic in artificial wetland system - Rahman, Md Ekhlasur; Mahmud, Khairil; Uddin, Md Kamal; Shamsuzzaman, S. M.; Abd Shukor, Mohd Yunus; Abd Ghani, Siti Salwa; Akter, Amaily; Nabayi, Abba; Sadeq, Buraq Musa; Chompa, Sayma Serine; Halmi, Mohd Izuan Effendi (Taylor and Francis Ltd., 2025)
The increasing demand for sustainable, robust, and cost-efficient arsenic (As) treatment techniques strengthens the implementation of new constructed wetland (CW) designs like aerated CWs in the agricultural sector. The aim was to assess and contrast the influence of various aeration rates on As elimination in subsurface flow CW utilizing Pennisetum purpureum plants for treating As-polluted sand. This study consisted of an experiment with 16 subsurface flow CW, operating at different As concentrations of 0, 5, 22, and 39 mg kg−1 and aeration rates of 0, 0.18, 1, and 2 L min−1. The highest elimination of As from treatment sand in the subsurface flow CWs was 96.19 ± 3.09%, 93.95 ± 2.17%, and 91.91 ± 1.92% for 5, 22, and 39 mg kg−1 As, respectively, at 0.18 L min−1 aeration. A negative influence of As pollution on growth was detected in the 0, 1, and 2 L min−1 aeration but Pennisetum purpureum grows well in polluted sand with 0.18 L min−1 aeration. Bacterial population and different enzyme activity showed statistically significant differences with 0, 0.18, 1, and 2 L min−1 aerations at all As levels. These results suggest that this treatment can be used for As phytoremediation in anthropogenically polluted environments due to its high capability to uptake As.